Demonstration that the Neurospora crassa mutation un-4 is a single nucleotide change in the tim16 gene encoding a subunit of the mitochondrial inner membrane translocase - Aric Wiest; Michael Plamann; Kevin McCluskey (Fungal Genetics Reports, 2008)
The Neurospora crassa temperature sensitive mutation known as un-4 has been shown by a map-based complementation approach to be a single nucleotide change in the open reading frame of the mitochondrial inner membrane translocase subunit tim16 (NCU05515).